Enhancing Internal Controlling Mechanism of Halal Industry: The Proposed Study on the Needs for External Halal Audit - Muhammad Iqmal Hisham Kamaruddin; Nurul Aini Muhamed; Mustafa Mohd Hanefah (Universiti Sains Islam Malaysia, 2024)
Halal industry in Malaysia is centralized at the Federal scope, with Jabatan Kemajuan Islam Malaysia (JAKIM) leads the role of the monitoring and supervision. Although JAKIM is recognised as the pionner in the Halal industry, issues arising in the Halal industry challenge the regulators on the effectiveness of the current Halal assurances especially in controlling and monitoring the industry and ensuring the Halal status of the products and services. Thus, the aims of this study is to examine the needs of external Halal auditing as to support the existing internal Halal auditing process to give better assurances in the Halal industry in Malaysia.